Method for in-situ growth of perovskite nanoparticles in carbonized polymer dot matrix
By in situ growing perovskite nanoparticles in a carbonized polymer dot matrix and using a microwave synthesis method to form core-shell structured CsPbBr3@CPDs, the problems of high preparation cost and poor stability of perovskite nanocrystals in liquid crystal displays are solved, and efficient and stable on-chip display applications are achieved.
Patent Information
- Application Number
- CN202510742158.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-05-22
- Filing Date
- 2025-06-05
- Publication Date
- 2025-09-12
AI Technical Summary
Existing perovskite nanocrystals have problems in liquid crystal displays, such as high preparation cost, low absorption coefficient, and poor stability. In particular, in on-chip structures, they are easily affected by high temperature and light radiation, resulting in luminescence quenching, making it difficult to meet practical application requirements.
A microwave synthesis method was used to in situ grow perovskite nanoparticles in a carbonized polymer dot matrix. By forming a core-shell structure of CsPbBr3@CPDs, the non-conjugated cross-linked network structure of CPDs was used to passivate the perovskite surface, thereby improving its absorption coefficient and photoluminescence quantum yield, and extending the phosphorescence lifetime through energy transfer.
The CsPbBr3@CPDs material has achieved high luminous efficiency and strong thermal stability, which can cover 91.3% of the Rec. 2020 color gamut in on-chip displays and is suitable for commercial white light diodes and information anti-counterfeiting materials.
Smart Images

Figure CN120624003A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to new material technology and relates to a method for in-situ growth of perovskite nanoparticles in a carbonized polymer dot matrix, specifically to in-situ growth of high-quality perovskite nanoparticles in a carbonized polymer dot matrix for on-chip display. Background Art
[0002] Compared to traditional liquid crystal displays (LCDs), quantum dot (QD)-enhanced liquid crystal displays (QD-LCDs) demonstrate superior color reproduction, color range, energy consumption, and lifespan. They have been widely researched and are gradually entering the market [Perovskite Quantum Dots for Application in High Color Gamut Backlighting Display of Light-Emitting Diodes]. Currently, the device structure of a QD-LCD typically consists of an LED backlight (blue GaN chip), a light guide plate, a brightness enhancement film, a diffuser film, upper and lower polarizers, thin-film transistors, liquid crystals, color filters, and green and red quantum dots [Liquid crystal display and organic light-emitting diode display: present status and future perspectives]. Quantum dots, as the light source, play a key role in QD-LCDs.
[0003] Generally speaking, quantum dot backlight structures can be categorized into three types: on-film QDs, on-edge QDs, and on-chip QDs [Quantum dots: The ultimate down-conversion material for LCD displays]. The on-film QDs structure is the most commonly used and established, with quantum dots encapsulated in a brightness enhancement film (QDEF) positioned directly above the light guide plate [Perovskite super-particles for commercial displays]. Although this structure has a minimal impact on blue LEDs, the increasing size of display panels necessitates a large number of quantum dots, leading to rising costs and limiting large-scale production and application. In the on-edge QDs structure, quantum dots are encapsulated in strips that fit over the sides of the blue LED and light guide plate, reducing heat and light radiation from the blue LED and lowering quantum dot consumption. However, current quantum dot glass tube assembly is difficult, and the packaging technology is complex, resulting in low quantum dot luminous efficiency and hindering practical application. In the QDs on-chip structure, quantum dots directly replace the phosphor on the LED chip. While this simple structure and low dosage make it a low-cost approach, the quantum dots in the on-chip package are susceptible to high temperatures and light radiation, leading to emission quenching and degradation. Therefore, the search for quantum dots with high luminous efficiency and strong thermal stability has been a hot research topic in this field [Stability of Quantum Dots, Quantum Dot Films, and Quantum Dot Light-Emitting Diodes for Display Applications].
[0004] Among the commonly used quantum dot (QDs) display materials, CdSe and InP have the advantages of tunable emission wavelength, narrow half-width and excellent stability, so they are widely used in the field of quantum dot enhanced liquid crystal displays (QD-LCDs) [Quantum Dots for Display Applications]. However, due to the toxicity of Cd and the expensive phosphorus precursors, these factors limit their further application in this field [Remote-type, high-color gamut white light-emitting diode based on InP quantum dot color converters]. In 2015, all-inorganic lead halide perovskite nanocrystals (CsPbX3) were first reported, which subsequently attracted widespread attention from researchers around the world to perovskite nanocrystals. Due to their ideal emission wavelength, narrow half-width and high quantum yield, CsPbX3 nanocrystals are very suitable for QD-LCDs. However, in actual display applications, perovskites face the following problems: (1) The cost of perovskite preparation is high. The most commonly used synthesis strategy for CsPbX3 nanocrystals is hot injection, which is mainly limited to laboratory-scale synthesis. The reaction conditions are harsh, including inert atmosphere and high temperature, and a tedious purification process with at least two centrifugation steps is required. Expensive solvents such as n-octadecane, toluene, n-hexane and ethyl acetate are required during the preparation and purification process. The product yield is low, and most of the precursors are wasted. Therefore, there is an urgent need to develop mild, simple, low-cost and high-yield synthesis methods to achieve the industrialization of CsPbX3 nanocrystals. (2) Perovskite powders exhibit low absorption coefficients and PLQY. The interaction between the surface ligands commonly used in this solid powder and the nanocrystals is relatively loose and easily destroyed. The loss of surface ligands leads to the aggregation of nanocrystals, and due to the reabsorption effect, the aggregated nanocrystals reduce the PLQY. In addition, due to the presence of many defects inside the powder, an inappropriate matrix may absorb a large number of photons, resulting in a decrease in the excitation light absorbed by the nanocrystals in the overlapping region of the excitation spectrum, thereby reducing the absorption coefficient. (3) Perovskite has poor stability. As an ionic crystal, it is easy to decompose under conditions such as water, oxygen, heat and light, resulting in structural damage. Especially in On-Chip applications, due to the direct influence of strong blue light, during continuous operation, its ligands are continuously removed by the heat generated by photon excitation, which eventually leads to luminescence quenching. In 2016, Liu et al. successfully prepared mesoporous silica-coated perovskite quantum dots for the first time, achieving a wider color gamut in On-Chip LED devices, providing new possibilities for backlight displays. In 2022, Li et al. used anions (SO4 2- OH - 、F -) passivation strategy to suppress the quenching behavior of CsPbBr3 perovskite nanocrystals, successfully realizing high-temperature stable white light-emitting diode (WLED) applications. Although encapsulation and passivation can significantly improve the durability of CsPbX3 nanocrystals, actual QD-LCDs based on perovskite on-chip have not been reported and do not meet the requirements of practical applications. Summary of the Invention
[0005] This study employed a simple microwave synthesis method to successfully synthesize CsPbBr3@CPDs powders with high luminescence efficiency, large absorption coefficient, and strong thermal stability. The P=O functional groups on the CPDs surface effectively passivate the perovskite, significantly increasing the perovskite powder's photoluminescence quantum yield (PLQY) to ~95%. The CsPbBr3 nanoparticles grown within the CPDs exhibit an extremely high absorption coefficient and, through energy transfer, a phosphorescence lifetime of up to 425 μs. This discovery is expected to promote their widespread application in future information security and phosphorescent light-emitting diodes. As highly non-conjugated, cross-linked networks, CPDs stabilize the CsPbBr3 nanoparticles within them by forming a core-shell structure, effectively preventing damage to the perovskite nanoparticles from high temperatures and continuous light exposure. Finally, the researchers successfully applied these perovskite nanocrystals to commercial white light-emitting diodes (WLEDs) and on-chip displays, achieving 91.3% color gamut coverage of the Rec. 2020 standard.
[0006] The present invention adopts the following technical solutions.
[0007] A method for in-situ growth of perovskite nanoparticles in a carbonized polymer dot matrix comprises the following steps: heating a system containing a perovskite raw material and a carbonized polymer precursor to achieve in-situ growth of perovskite nanoparticles in the carbonized polymer dot matrix.
[0008] The present invention discloses carbonized polymer dot / perovskite nanoparticles prepared by the method of in-situ growing perovskite nanoparticles in a carbonized polymer dot matrix.
[0009] The present invention discloses the application of the carbonized polymer dots / perovskite nanoparticles as or in the preparation of luminescent materials.
[0010] The present invention discloses the application of the carbonized polymer dots / perovskite nanoparticles in the preparation of light-emitting devices.
[0011] The present invention discloses the application of the carbonized polymer dots / perovskite nanoparticles in the preparation of anti-counterfeiting materials.
[0012] The present invention discloses a light-emitting device, comprising the carbonized polymer dots / perovskite nanoparticles.
[0013] In the present invention, the system containing the perovskite raw material and the carbonized polymer precursor includes the perovskite raw material, the carbonized polymer precursor, a solvent and an acid.
[0014] In the present invention, the perovskite raw materials are conventional products, including cesium salts and lead salts, such as cesium halides and lead acetate. Preferably, the system containing the perovskite raw materials and the carbonized polymer precursor of the present invention does not include 1-octadecene, oleic acid, and oleylamine.
[0015] In the present invention, the carbonized polymer precursor includes one or more of dicyandiamide, cyanamide, melamine, cyanoguanidine, and thiourea.
[0016] In the present invention, the acid includes one or more of phosphoric acid, pyrophosphoric acid, tripolyphosphoric acid and polyphosphoric acid.
[0017] In the present invention, the solvent includes water; preferably, the solvent is water.
[0018] In the present invention, the heating is microwave heating; preferably, the power of the microwave heating is 600 W-1200 W, and the heating time is 60 s-180 s.
[0019] The main advantage of the present invention is the preparation of highly stable CsPbBr3@CPDs, which can be directly used in commercial on-chip displays. Commercial on-chip displays are a very important part of the backlight display field. They have a simple structure, high light energy rate and low cost. However, they have high requirements for the fluorescence efficiency and stability of the material. Perovskite nanocrystals can be used in backlight displays due to their excellent optical properties. However, perovskite powder has a low absorption coefficient, low fluorescence yield and poor stability under continuous operation, which is not conducive to its application in on-chip displays. The present invention discloses a simple microwave-assisted heating method, which grows perovskite nanoparticles in a carbonized polymer dot matrix in a one-step method. The highly non-conjugated cross-linked network structure of CPDs can effectively passivate the perovskite surface and improve its absorption coefficient and PLQY. The CsPbBr3@CPDs prepared by the present invention exhibit a quantum yield of up to 95% and a phosphorescence lifetime of up to 425μs, which can be used in future information anti-counterfeiting and phosphorescent LEDs. Due to the core-shell structure protection constructed by CPDs, the capture activation energy of perovskite nanocrystals can also be improved, and the fluorescence intensity at 373k can still maintain more than 60% of the initial value. Ultimately, the present invention successfully applied this excellent and highly stable material to on-chip display for the first time, and its color gamut covered 91.3% of the Rec. 2020 standard. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1The formation process of CsPbBr3@CPDs, including (a) in situ fluorescence spectroscopy observation of the formation of CsPbBr3@CPDs. (b) UV absorption and fluorescence emission spectra of the final CsPbBr3@CPDs. (c) Photograph of CsPbBr3@CPDs powder under sunlight. (d) Photograph of the CsPbBr3@CPDs powder formation process under UV light (λ = 365 nm).
[0021] Figure 2 Schematic diagram of the preparation and characterization of CsPbBr3@CPDs, including (a) schematic diagram of the microwave-assisted synthesis of CsPbBr3@CPDs. (b) TEM image of CsPbBr3@CPDs, with the inset showing the corresponding HRTEM image. The scale bar is 2 nm.
[0022] Figure 3 is the size distribution of CsPbBr3@CPDs.
[0023] Figure 4 is CsPbX3@CPDs, where (a) CsPbCl2Br1@CPDs, CsPbCl 1.5 Br 1.5 @CPDs, CsPbCl1Br2@CPDs, CsPbBr2I1@CPDs, CsPbBr 1.5 I 1.5 Photos of @CPDs and CsPbI3@CPDs under sunlight (top) and 365 nm UV light (bottom). (b) CsPbCl 1.5 Br 1.5 @CPDs、CsPbCl1Br2@CPDs、CsPbBr 1.5 I 1.5 Fluorescence spectra of @CPDs and CsPbI3@CPDs.
[0024] Figure 5 It serves as the XRD standard for CsPbBr3@CPDs and dicyandiamide, as well as the reference standard for orthorhombic CsPbBr3 (ICSD#01-072-7929) and monoclinic dicyandiamide (ICSD#11-703).
[0025] Figure 6 FTIR spectrum of CsPbBr3@CPDs.
[0026] Figure 7 XPS spectra of CsPbBr3@CPDs: (a) complete elements, (b) C 1s, (c) N 1s, (d) O 1s, (e) P 2p, (f) Cs3d, (g) Pb 4f, and (h) Br 3d.
[0027] Figure 8 This is the Raman spectrum of CsPbBr3@CPDs.
[0028] Figure 9 Schematic diagram of the structural formula of CPDs matrix formation.
[0029] Figure 10 Photos of CsPbBr3 nanocrystalline powder prepared without adding phosphoric acid under sunlight (a) and 365 nm ultraviolet light (b).
[0030] Figure 11 (a) Fluorescence spectra and (b) absorption of CsPbBr3@CPDs prepared with different amounts of H3PO4. The inset shows a series of photographs of the samples under sunlight (left) and 365 nm UV light (right). (c) Time-resolved fluorescence emission spectra of CsPbBr3@CPDs prepared with different amounts of H3PO4. (d) XRD patterns and (e) PLQY of the corresponding samples synthesized with different amounts of H3PO4.
[0031] Figure 12 Photographs of (a) CPDs and (b) CsPbBr3@CPDs at different delay times after turning off the UV light (λ = 365 nm). (c) Phosphorescence spectra of CPDs and CsPbBr3@CPDs. (d) Schematic diagram of the fluorescence, phosphorescence, and energy transfer processes between CPDs and CsPbBr3.
[0032] Figure 13 Time-resolved phosphorescence spectra of pure CPDs and CsPbBr3@CPD, with peaks at 473 nm and 525 nm, respectively.
[0033] Figure 14 Fluorescence, phosphorescence and time-resolved phosphorescence spectra of CsPbBr3 (HI-CsPbBr3) nanocrystals prepared by hot injection and mixed with CPDs.
[0034] Figure 15 Time-dependent fluorescence spectra (λ = 365 nm) of CsPbBr3@CPDs treated with different phosphoric acid treatments: (a) 200 μL-CsPbBr3@CPDs, (b) 300 μL-CsPbBr3, and (c) HI-CsPbBr3 nanocrystals as the temperature rises from 293 K to 373 K. Corresponding fluorescence integrated intensities for (d) 200 μL-CsPbBr3@CPDs, (e) 300 μL-CsPbBr3, and (f) HI-CsPbBr3 nanocrystals. Solid lines are fitted curves.
[0035] Figure 16 For use 180 oPreparation process of CsPbBr3@CPDs@PS polymer film produced by C extruder.
[0036] Figure 17 (a) Luminescence spectrum of a WLED based on a commercial blue LED chip, CsPbBr3@CPDs, and KSF:Mn phosphor. Inset: Photograph of the device structure. (b) Photograph of the WLED operating at 8 mA. (c) Color coordinates of the WLED. (d) PL spectrum changes of the WLED under continuous current (8 mA) excitation.
[0037] Figure 18 (a) Schematic diagram of the structure of a commercial on-chip display based on a blue LED, CsPbBr3@CPDs, and KSF:Mn phosphor. (b) Display performance and (c) color gamut of the on-chip device. DETAILED DESCRIPTION
[0038] This invention uses a simple microwave synthesis method to successfully synthesize CsPbBr3@CPDs powder with high luminescence efficiency, large absorption coefficient, and strong thermal stability. Carbonized polymer dots (CPDs) are a new type of fluorescent carbon dots. They not only inherit the excellent luminescence properties and outstanding thermal stability of carbon dots, but also possess a polymer-like matrix effect, replacing supramolecular interactions with covalent bonds, thereby significantly enhancing fixation. Due to their rich non-conjugated groups and highly cross-linked network structure, this invention provides a novel, highly stable, and suitable matrix for perovskite nanocrystals, improving the stability and luminescence efficiency of perovskites.
[0039] CsPbX3@CPDs were successfully prepared by a simple microwave heating method. Figure 2 Taking a) as an example, first, cesium bromide, lead acetate, dicyandiamide, and phosphoric acid are added to water to obtain a transparent white solution as a reaction precursor; then, the reaction precursor is placed in a microwave oven and reacted at 600 W-1200 W for 1-3 minutes; after evaporation of the solution, a yellow-green powder is formed.
[0040] The experimental reagents involved in the present invention are all existing products, and the specific preparation operations and performance tests are all conventional technologies. Cesium halide (CsX (X = Cl, Br, I), 99.9%, Macklin), lead acetate (Pb(CH3COO)2, 99.99%, Aladdin), dicyandiamide (C2H4N4, 99%, Macklin), phosphoric acid (H3PO4, 85 wt%, Aladdin), cesium carbonate (Cs2CO3, 99.998%, Alfa Aesar), lead halide (PbX2 (X = Cl, Br, I), 99.999%, Alfa Aesar), 1-octadecene (ODE, C 18 H 36 , 90%, Alfa Aesar), oleic acid (OA, C 18 H 34 O2, 90%, Alfa Aesar), oleylamine (OAm, C 18 H 37 N, 80-90%, Acros) were used as received without further purification. 4+ ) and polystyrene (PS) particles were provided by Suzhou Mesolight Nanotechnology Co., Ltd. The QD-Chip display prototype was provided by Suzhou AU Optronics Corp.
[0041] Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images were obtained using a TALOS 200X at 220 kV. Photoluminescence (PL) and phosphorescence spectra were recorded on a FLUOROMAX-4 fluorescence spectrometer using a xenon lamp. Solid-state UV-visible absorption spectra were collected in the 300–800 nm range using an Evolution 220 spectrophotometer. X-ray diffraction (XRD) patterns were measured on an Empyrean diffractometer (PANalytical) using a Cu Kα source (λ = 1.54056 Å). PLQY was measured using a Quantaurus-QY Plus C13534-11 (HAMAMATSU). Fluorescence and phosphorescence lifetimes were measured using a HORTB-FM-2015 spectrometer. Fourier transform infrared (FTIR) spectra were obtained using a Bruker Vertex V70 spectrometer. X-ray photoelectron spectroscopy (XPS) information was collected using an X-ray photoelectron spectrometer (Thermo Fisher) equipped with a single Al Ka source (1486.7 eV). Powder fluorescence was collected using an illuminometer (OHSP-350) manufactured by Hangzhou Hongpu Optoelectronics Technology in the range of 380–780 nm.
[0042] Example 1 Preparation of CsPbX3@CPDs To synthesize CsPbBr3@CPDs, 0.0638 g of cesium bromide, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixture was then heated in a microwave oven (Midea, 750 W) for 135 s and allowed to cool naturally, yielding a pale yellow-green powder, CsPbBr3@CPDs.
[0043] According to the above method, different amounts of phosphoric acid (50 μL, 100 μL, 150 μL and 300 μL) were added to the reaction system to obtain CsPbBr3@CPDs, which were named P 50 -CsPbBr3@CPDs、P 100 -CsPbBr3@CPDs、P 150 -CsPbBr3@CPDs、P 200 -CsPbBr3@CPDs and P 300 -CsPbBr3@CPDs.
[0044] To synthesize CsPbCl2Br1@CPDs, 0.0213 g of cesium bromide, 0.0336 g of cesium chloride, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixture was then heated in a microwave oven (Midea, 750 W) for 135 s and allowed to cool naturally to obtain a pale white powder, CsPbCl2Br1@CPDs.
[0045] Synthesis of CsPbBr 1.5 Cl 1.5 @CPDs. 0.0319 g of cesium bromide, 0.0253 g of cesium chloride, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixed solution was then placed in a microwave oven (Midea, 750 W) and heated for 135 s. After cooling naturally, a light green powder was obtained, which was CsPbBr 1.5 Cl 1.5 @CPDs.
[0046] To synthesize CsPbBr2Cl1@CPDs, 0.0426 g of cesium bromide, 0.0168 g of cesium chloride, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixture was then heated in a microwave oven (Midea, 750 W) for 135 s and allowed to cool naturally to obtain a green powder, CsPbBr2Cl1@CPDs.
[0047] To synthesize CsPbBr2I1@CPDs, 0.0426 g of cesium bromide, 0.0260 g of cesium iodide, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixed solution was then heated in a microwave oven (Midea, 750 W) for 135 s and allowed to cool naturally to obtain a pink powder, CsPbBr2I1@CPDs.
[0048] Synthesis of CsPbBr 1.5 I 1.5 @CPDs. 0.0354 g of cesium bromide, 0.0346 g of cesium iodide, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixed solution was then placed in a microwave oven (Midea, 750 W) and heated for 135 s. After cooling naturally, a red powder was obtained, which was CsPbBr. 1.5 I 1.5 @CPDs.
[0049] To synthesize CsPbI3@CPDs, 0.0779 g of cesium iodide, 0.0379 g of lead acetate, 0.5 g of dicyandiamide, and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixture was then heated in a microwave oven (Midea, 750 W) for 135 s and allowed to cool naturally to obtain a black-red powder, CsPbI3@CPDs.
[0050] The properties of the above different products are shown in Table 1 and Table 2 below.
[0051] Table 1 Comparison of performance of CsPbBr3@CPDs prepared with different amounts of phosphoric acid
[0052] Table 2 Comparison of performance of CsPbX3@CPDs prepared with different halogen ratios
[0053] Comparative Example Synthesis of Comparative Sample HI-CsPbBr3 Nanocrystals According to existing reports, HI-CsPbBr3 nanocrystals were synthesized by a modified hot injection method. 0.2 g Cs2CO3, 1.25 mL OA and 20 mL ODE were mixed in a 50 mL three-necked flask to prepare a cesium oleate solution. o C for 1 hour, then heated to 150°C under N2 atmosphere. oC. In a 25 mL three-necked flask, OAm (1.23 mmol), OA (1.17 mmol), ODE (5 mL) and PbBr2 (0.073 g) were added and then heated to 160 C under N2 atmosphere. o C. Next, 0.4 mL of hot cesium oleate solution was injected into the PbBr2 solution, and then the bottle was placed in ice water to cool to room temperature. The mixed solution was centrifuged at 9000 rpm for 5 minutes, and then the supernatant was collected and dispersed in 10 mL of hexane to obtain HI-CsPbBr3 nanocrystal dispersion.
[0054] The formation process of CsPbBr3@CPDs was observed by In-Situ fluorescence spectroscopy (see Figure 1 For the first few seconds, the powder exhibits little or no fluorescence. Over time, the fluorescence of the CsPbBr3@CPDs gradually increases, ultimately emitting bright green light under 365 nm UV light. The emission wavelength is 522 nm, and the half-width at half maximum is only 22 nm. This material has the potential for widespread application in QD-LCD displays.
[0055] The microwave heating method has the advantages of high heating rate, good repeatability and low energy consumption. Compared with the traditional hot injection method, the solvent used in the present invention is water, which is more environmentally friendly and cheaper. All raw materials are commercial products, making this preparation strategy easier to promote and apply in industry. It is worth noting that the method of the present invention does not require tedious purification steps, thus saving processing and chemical costs. Through cost calculation, the reagent cost of CsPbBr3@CPDs prepared by the present invention is only ¥1.17 g -1 , while the reagent cost of hot injection method is as high as ¥ 433.13 g -1 (See Tables 3 and 4.) This scalable, low-cost, and efficient method for the direct synthesis of lead halide perovskite nanocrystals has potential industrial applications.
[0056] Table 3 Chemical reagents for the preparation of CsPbBr3@CPDs via microwave-assisted heating
[0057] In a 20 mL batch, 0.8 g of CsPbBr3@CPDs powder can be obtained, so the cost of CsPbBr3@CPDs is 1.17 yuan / g.
[0058] Table 4 Chemical reagents for preparing CsPbBr3 nanocrystals by conventional hot injection method
[0059] In a 20 mL batch, 0.083 g of CsPbBr3 nanocrystals can be obtained, so the cost of CsPbBr3 nanocrystals is 433.13 yuan / g.
[0060] The morphology of CsPbBr3@CPDs was characterized in detail by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). Figure 2 As shown in b. CsPbBr3 nanoparticles are evenly distributed in the covalently cross-linked network polymer spheres. Each CsPbBr3 nanoparticle is monodispersed and coated with a thin layer of CPDs without any agglomeration. The average size is about 3.71 nm (see Figure 3 ). High-resolution transmission electron microscopy observation showed that the interplanar spacing was 0.41 nm, which corresponds to the (110) crystal plane of orthorhombic phase CsPbBr3. The composite structure was characterized by high-angle annular dark-field transmission electron microscopy (HAADF-STEM) and elemental mapping. Dark-field photography showed that small CsPbBr3 particles were uniformly dispersed in CPDs to form a core-shell structure, providing direct evidence for the improved stability of CsPbBr3. Elemental mapping showed that Cs, Pb, and Br were uniformly distributed within the spheres. This evidence confirms that the method of the present invention can quickly prepare a large amount of CsPbBr3@CPDs powder at one time. In addition, the present invention successfully controlled the ratio of different perovskites and halogens to prepare CsPbX3@CPDs (X=Cl / Br, Br, Br / I, and I) that emit light in the visible light spectrum, see Figure 4 Among them, CsPbCl 1.5 Br 1.5 @CPDs、CsPbCl1Br2@CPDs、CsPbBr 1.5 I 1.5 The fluorescence emission peaks of @CPDs and CsPbI3@CPDs are 470 nm, 520 nm, 618 nm, and 680 nm, respectively. This energy- and material-efficient method has great universality.
[0061] Traditional CPDs preparation methods usually use solvent thermal method or high temperature heating method. In order to further verify that the method of the present invention successfully prepared CPDs, in-depth characterization was carried out using XRD, infrared, XPS, Raman and other spectral techniques. The first is XRD analysis, such as Figure 5 As shown, it was observed that under the action of microwave, dicyandiamide o -30 o The main peaks in the range gradually disappeared, while in the CsPbBr3@CPDs sample, a broader peak appeared at 27.5 oThis may correspond to the (002) crystal plane of graphite, suggesting the formation of CPDs. In addition, it can be observed from the XRD spectrum that the main peak of CsPbBr3@CPDs (15.2 o , 21.5 o , 30.8 o , 37.6 o , 43.7 o ) corresponded to the orthorhombic phase CsPbBr3 (# 01-072-7929). These analytical results strengthened the evidence for the successful synthesis of CPDs.
[0062] Under the action of microwaves, dicyandiamide and phosphoric acid undergo an esterification and dehydration reaction to form CPDs, which become an ideal matrix for CsPbBr3 nanoparticles. In order to characterize it more comprehensively, Fourier transform infrared spectroscopy (FTIR) was used to reveal the surface properties of the CPDs matrix, as shown in the following figure: Figure 6 As shown. From the infrared spectrum, it can be observed that the surface of CPDs is rich in various functional groups, and the main characteristic peaks include 3331 cm -1 (NH), 3082 cm -1 (CH), 1728 cm -1 (C=O), 1653 cm -1 (C=N), 1508 cm -1 (C=C), 1234 cm -1 (P=O), 1065 cm -1 (PO), 968 cm -1 (PN) and 864 cm -1 (CH). These abundant functional groups effectively passivate CsPbBr3 nanoparticles. Compared with the traditional oleylamine and oleic acid ligands, this passivation effect significantly improves the efficiency and stability of perovskite nanocrystals. At the same time, X-ray photoelectron spectroscopy (XPS) was used to further characterize it. The results are as follows Figure 7As shown in Figure 3, the C 1s band can be fitted into three peaks at 284.6 eV, 285.9 eV, and 288.4 eV, corresponding to C-C, C=N, and C=O, respectively. The N 1s band contains three peaks at 398.6 eV (N-(C)3), 399.7 eV (CN=C), and 400.1 eV (NH). The O 1s band contains three sub-peaks at 530.6 eV, 531.5 eV, and 532.4 eV, corresponding to P=O, C=O, and PO, respectively. The P 2p band can be fitted into two peaks at 133.3 eV (PO / P=O) and 134.3 eV (PN). The XPS spectra of Cs 3d, Pb 4f, and Br 3d in CsPbBr3 nanocrystals are consistent with those of conventional CsPbBr3 nanocrystals. In order to further study the interaction between CsPbBr3 and CPDs, Raman spectroscopy of CsPbBr3@CPDs was also performed. Figure 8 , the results showed that at 697 cm -1 , 1011cm -1 and 1147 cm -1 There are major peaks at 697 cm -1 The strong peak is mainly attributed to the ν (C--Br) vibration, indicating that there is an interaction between CPDs and Br- of CsPbBr3. The other two peaks are 1011 cm -1 and 1147 cm -1 This series of characterization results provides strong support for a deeper understanding of the CsPbBr3@CPDs composite structure.
[0063] Under the action of microwaves, dicyandiamide can be used as a carbon source and a nitrogen source for carbonization and doping, while phosphoric acid can be used as a catalyst for dehydration and deamination and a cross-linking agent for polymerization. By combining the -NH2 group in dicyandiamide with phosphoric acid to form long-chain polymers, such as Figure 9 As shown, deamination and dehydration reactions then occur between the long-chain polymers, ultimately forming CPDs with a covalently cross-linked framework. During this process, cesium bromide and lead acetate react with them, and high quantum yield CsPbBr3 nanoparticles grow in the CPDs matrix.
[0064] The quantum yield (PLQY) of CsPbBr3@CPDs powder was tested and found to be as high as 95%. Under the same conditions, a solution without phosphoric acid molecules (phosphoric acid was omitted based on Example 1) was completely evaporated and showed blue fluorescence under UV light, proving that no CsPbBr3 nanoparticles with high luminous efficiency were formed (see Figure 10 ). Therefore, phosphoric acid plays an important role in the molecular polymerization process.
[0065] Different amounts of phosphoric acid (50 μL, 100 μL, 150 μL, 200 μL, and 300 μL) were added to the reaction system. Figure 11 As shown in a, under 50 μL conditions, the powder fluorescence is weak, the emission peak is broadened, and the position is about 510 nm. As the amount of phosphoric acid increases, the fluorescence gradually increases, and the emission peak gradually red-shifts to about 525 nm. At the same time, the fluorescence quantum yield (PLQY) gradually increases. However, under 300 μL phosphoric acid conditions, the PLQY of CsPbBr3@CPDs does not further increase, but instead decreases. A similar phenomenon is also observed in the absorption spectrum ( Figure 11 b), the absorption peak gradually red-shifted. Their fluorescence lifetime was tested by time-resolved fluorescence spectroscopy. Figure 11 As shown in Figure c, the fluorescence lifetime gradually increases and then decreases with increasing phosphoric acid content, reaching a lifetime of 34.5 ns at 200 μL. Compared to perovskite nanocrystals prepared by conventional hot injection (5.5 ns), this method exhibits a longer fluorescence lifetime, suggesting reduced surface defects and suppressed non-radiative recombination of CsPbBr3, consistent with the PLQY results. X-ray diffraction (XRD) analysis of CsPbBr3@CPDs synthesized with varying amounts of phosphoric acid revealed that the crystallinity of CsPbBr3 in the samples gradually increased with increasing phosphoric acid content, demonstrating that phosphoric acid molecules facilitate the formation of CsPbBr3 nanoparticles. First, under microwave conditions, dicyandiamide and phosphoric acid undergo a dehydration-esterification reaction, forming a covalently cross-linked polymer network. Within this structure, phosphoric acid plays a key role, connecting the entire polymer network through P=O bonds, thereby enhancing the PLQY of CsPbBr3. In the absence of phosphoric acid, dicyandiamide cannot form a network-like polymer molecule and the fluorescence quantum yield is low.
[0066] In order to verify that CsPbBr3@CPDs exhibit such a high photoluminescence efficiency (PLQY), the high absorption coefficient of CsPbBr3 in CPDs was analyzed by phosphorescence. Pure CPDs exhibited long-lasting phosphorescence, which was visible to the naked eye for up to about 7 seconds. Figure 12 As shown. The photons continuously emitted by the CPDs in CsPbBr3@CPDs are then absorbed by the excitons generated in CsPbBr3, and then the perovskite emits photons through exciton recombination, forming a nearly visible 4-second phosphorescence. Phosphorescence spectrum tests show that the phosphorescence intensity of CsPbBr3 nanoparticles is 55% of that of pure CPDs, indicating that it has a high conversion efficiency. Their phosphorescence lifetime was also tested, as shown in Figure 13 As shown, the phosphorescence lifetimes in pure CPDs and CsPbBr3@CPDs are 468 μs and 425 μs, respectively.
[0067] For better comparison, CsPbBr3 (labeled as HI-CsPbBr3) was prepared by hot injection method, and this nanocrystal was mixed with pure CPDs to test their phosphorescence intensity and phosphorescence lifetime, as shown in Figure 2. Figure 14 As shown in Figure 2 . Under the same test conditions, the emission wavelength of HI-CsPbBr3 nanocrystals is around 508 nm. In comparison, the phosphorescence intensity is very low, with a phosphorescence lifetime of only 3.87 μs. In contrast, the CsPbBr3 nanoparticles in the CsPbBr3@CPDs prepared in this invention exhibit higher phosphorescence intensity and lifetime after the radiation reabsorption process of energy transfer. This demonstrates that the product of this invention possesses high PLQY characteristics.
[0068] In summary, the CsPbBr3@CPDs prepared in this invention not only exhibit excellent light absorption coefficient but also high room-temperature phosphorescence efficiency. This material has broad application prospects, especially in information anti-counterfeiting and phosphorescent light-emitting diodes.
[0069] Preparation of CPDs: 0.5 g of dicyandiamide and 0.2 mL of phosphoric acid were dissolved in 10 mL of deionized water. The mixed solution was then placed in a microwave oven (Midea, 750 W) and heated for 135 s. The mixture was then naturally cooled to room temperature to obtain white powder CPDs.
[0070] A mixture of HI-CsPbBr3 nanocrystals and pure CPDs was prepared directly by the impregnation method: the prepared HI-CsPbBr3 nanocrystals were dispersed in 5 mL of cyclohexane solution. 0.4 g of CPDs powder was added to a 10 mL glass vial, and then 2 mL of 32 mg / mL HI-CsPbBr3 nanocrystal colloidal solution was added via a pipette, resulting in a 0.16:1 mixture ratio. The mixture was stirred on a magnetic stirrer for approximately 3 hours until the cyclohexane was completely evaporated, resulting in a mixture of HI-CsPbBr3 nanocrystals and pure CPDs.
[0071] One challenge facing fluorescent materials in display applications is high-temperature stability. These materials are subject to thermal quenching in sustained high-temperature environments, often due to surface trap states or thermally induced capture of activated carriers and phonon-assisted non-radiative quenching. For perovskite nanocrystals, due to their low trapping activation energy, these nanocrystals generate numerous defects as temperature increases, leading to a rapid decrease in fluorescence intensity. The present invention conducted variable-temperature fluorescence testing. Figure 15Figures a, b, and c show the fluorescence spectra of the prepared CsPbBr3@CPDs (200 μL, 300 μL) and HI-CsPbBr3 nanocrystals treated with different amounts of phosphoric acid in the range of 293 K to 373 K. It can be seen that the fluorescence of all samples decays at high temperatures. Notably, the sample treated with 200 μL of phosphoric acid exhibits high thermal stability, with its fluorescence intensity still retaining approximately 60% of its initial value at 373 K. This is in stark contrast to the sample treated with 300 μL of phosphoric acid, whose fluorescence intensity at 373 K is only 49% of its initial value. In contrast, the fluorescence intensity of HI-CsPbBr3 retains only 2% of its initial value at 373 K. The passivation of P=O by CsPbBr3 in CPDs enhances its ability to suppress thermal fluorescence quenching.
[0072] The carrier capture activation energy of CsPbBr3 was estimated by fitting the temperature-dependent values ( ΔE trap ), the fluorescence intensity was estimated by integrating the conventional Arrhenius formula, and the corresponding fitting curve was obtained by high temperature fitting. Figure 15 As shown in d, e, and f, different samples were obtained. ΔE trap From the figure, we can see that the ΔE trap The value is only 386 meV, which is due to the inherent defect states of the nanocrystals. However, after being treated with different amounts of phosphoric acid, the defect states of CsPbBr3@CPDs were successfully passivated, and the ΔE trap The improvement is significant, reaching 584 meV and 546 meV respectively, indicating that its thermal stability has been greatly improved.
[0073] Example 2 Preparation of CsPbBr3@CPDs@PS thin film by melt extrusion The conventional injection molding process was used for melt co-extrusion film formation. First, 10 g of polystyrene (PS) particles were weighed, then 1 g of CsPbBr3@CPD powder (10% loading) was added, and finally 1 mL of silicone oil was added to facilitate mixing of polystyrene and perovskite powder. Conventional mixing was used to obtain a mixture of CsPbBr3@CPDs@PS particles. The mixture was heated at high temperature (180 o CsPbBr3@CPDs@PS particles were placed in the injection molding extrusion machine and CsPbBr3@CPDs@PS film was prepared by melt co-extrusion.
[0074] The prepared CsPbBr3@CPDs have achieved significant improvements in photon quantum yield (PLQY) and stability, and are applied to industrial-grade melt extruders for film preparation. Figure 16 As shown in the figure, a certain amount of PS particles was selected, 10% CsPbBr3@CPDs was loaded onto the PS particles, and after uniform mixing, the mixture was directly fed into an extruder at approximately 180°C. As shown in the figure, after heating at 180°C, the prepared CsPbBr3@CPDs exhibited excellent thermal stability, and the film exhibited distinct green fluorescence under UV light. This highly stable material is expected to be widely used in future quantum dot diffusers or quantum dot light guides for QD-LCDs, significantly reducing industrial production costs.
[0075] Example 3 Preparation of On-Chip White Light Emitting Diode (WLED) Based on CsPbBr3@CPDs A red phosphor (KSF:Mn) was added to the bottom of a commercial blue LED (λ = 455 nm) chip, and then green-emitting CsPbBr3@CPDs powder was directly superimposed on the red phosphor layer. The blue LED light was turned on with a current intensity of about 8 mA to obtain a WLED.
[0076] The aforementioned experiments and tests fully demonstrate that the prepared CsPbBr3@CPDs exhibit excellent performance in high-temperature environments. To verify its potential in practical display applications, a white light emitting diode (WLED) device was successfully prepared using commercial red phosphor (KSF:Mn) as a red light source and CsPbBr3@CPDs as a green light source. See the schematic diagram for details. Figure 17 Under the excitation of a commercial blue LED chip (λ = 455 nm), KSF:Mn phosphor was first directly introduced, and then 1g of CsPbBr3@CPDs was added. Driven by a current of 8 mA, the WLED device produced strong white light emission, and its emission spectrum is shown in Figure 2. Figure 17 As shown in a, the luminous efficiency test result is 75.2 lm W -1 The obtained white light color point is (0.31, 0.33), which meets the standard of ideal WLED.
[0077] Further stability testing revealed that after 24 hours of continuous irradiation at a current of 8 mA, the CsPbBr3@CPDs exhibited excellent thermal stability, with only a 7% decrease in fluorescence intensity and virtually no shift in color point. These results demonstrate that the highly stable CsPbBr3@CPDs are comparable to commercial green phosphors, demonstrating their potential for practical applications.
[0078] Example 4 Preparation of QD-LCDs Device Based on CsPbBr3@CPDs QDs On-Chip The commercial LCD prototype was provided by AUO. A commercial blue LED chip (λ = 452 nm) was coated with red phosphor (KSF:Mn), and 0.5 g of CsPbBr3@CPDs powder was directly layered on top. This was then bonded to the edge of a light guide plate, followed by a diffuser film, brightness enhancement film, and TFT-LCD module. Further packaging completed the device.
[0079] Given the excellent stability of the materials in WLED, the above materials are directly applied to commercial On-Chip display technology, for example Figure 18 The red-emitting phosphor KSF:Mn and the green-emitting CsPbBr3@CPDs are encapsulated on a commercial LED chip. The device structure is shown in the figure. Figure 18 As shown in a. Under the excitation of a current intensity of 200 mA, the light guide plate generates white light, which then passes through the diffusion film, the brightness enhancement film, and the TFT-LCD panel to present a vivid and realistic image ( Figure 18 b). The color gamut calculation results are shown in Figure 18 c and Table 5 show that the display color gamut based on the CsPbBr3@CPDs prototype covers 91.3% of Rec. 2020. This experimental result demonstrates that the CsPbBr3@CPDs material exhibits superior performance in commercial on-chip displays with rich, vivid, and realistic colors.
[0080] Table 5 CIE coordinates of CsPbBr3@CPDs and Rec. 2020 standard.
[0081]
[0082] Color gamut (area ratio) is Figure 18 c The ratio of the RGB triangle area of the screen to the Rec. 2020 area, which is conventional technology.
[0083] This study successfully prepared high-quality CsPbBr3@CPDs powder using a rapid, simple, and low-energy microwave-assisted heating method. This preparation method not only significantly reduces raw material costs but also has important guiding significance for practical applications. Furthermore, the resulting CPDs possess a non-conjugated, highly cross-linked polymeric network composed of P=O, which, as a matrix for CsPbBr3, significantly passivates the perovskite surface. This passivation significantly improves the photoluminescence quantum yield (PLQY) and absorption coefficient of CsPbBr3. The prepared CsPbBr3@CPDs exhibit a moderate emission wavelength (522 nm), a narrow half-maximum width (22 nm), and an ultra-high PLQY (95%). Notably, CsPbBr3 achieves energy transfer via radiative reabsorption, resulting in exceptional phosphorescence intensity and a long lifetime, further demonstrating its superior light absorption properties. Furthermore, under the protection of CPDs, the thermal stability of CsPbBr3 is significantly enhanced. Ultimately, the superior performance of CsPbBr3@CPDs was successfully applied to WLED devices and commercial on-chip display technology, achieving a color gamut that covered 91.3% of the Rec. 2020 standard. These research results have injected new impetus into the advancement of perovskite nanocrystals in industrial display technology.
Claims
1. A method for in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix, characterized in that: The method comprises the following steps: heating a system containing a perovskite raw material and a carbonized polymer precursor to realize in-situ growth of perovskite nanoparticles in a carbonized polymer dot matrix.
2. The method for in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix according to claim 1, characterized in that: The system containing a perovskite raw material and a carbonized polymer precursor includes a perovskite raw material, a carbonized polymer precursor, a solvent and an acid.
3. The method for in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix according to claim 2, characterized in that: Perovskite raw materials include cesium salts and lead salts.
4. The method for in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix according to claim 2, wherein: The carbonized polymer precursor includes dicyandiamide; the acid includes phosphoric acid; and the solvent includes water.
5. The method for in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix according to claim 1, wherein: The heating is microwave heating. 6 . Carbonized polymer dots / perovskite nanoparticles prepared according to the method of in situ growth of perovskite nanoparticles in a carbonized polymer dot matrix according to claim 1 .
7. Use of the carbonized polymer dots / perovskite nanoparticles according to claim 6 as or in the preparation of a luminescent material.
8. Use of the carbonized polymer dots / perovskite nanoparticles according to claim 6 in the preparation of light-emitting devices.
9. Use of the carbonized polymer dots / perovskite nanoparticles according to claim 6 in the preparation of anti-counterfeiting materials.
10. A light-emitting device comprising the carbonized polymer dots / perovskite nanoparticles according to claim 6.